Determination of the Machine and Tractor Fleet Optimal Composition for a Model CottonTextile Cluster - M. T. Toshboltaev; M. R. Dzhiyanov (Сельскохозяйственные машины и технологии)
The authors showed that the cotton-textile cluster efficiency (the capacity of the machine-tractor fleet, cotton yield, the production profitability) largely depended on the use of the optimal number of tractors and agricultural machines. The existing methods (theoretical, graphic, economic and mathematical) were difficult for practical use and did not take into account the specifics of mechanized cotton growing processes. Therefore, it was important to develop a simple normative method for determining the optimal composition of the machine and tractor fleet for clusters, corresponding to the technological map for the production of raw cotton. (Research purpose) To calculate the required amount of agricultural machinery based on the established standards. (Materials and methods) The authors developed an algorithm for determining the standard coefficients of the equipment necessity per 1000 hectares of arable land. These coefficients for each type of equipment were established in the context of technological operations of growing cotton: plowing, soil preparing for sowing, sowing seeds, cultivating the soil between cotton rows, mechanized removal of growth points of the main stems and side branches of plants, defoliation with chemicals, machine harvesting and transportation of harvested cotton – raw. (Results and discussion) The authors proposed the term “model cotton-textile cluster”. They calculated the required amount of equipment for such a cluster with an area of 13,732 hectares. They determined the percentage of the machine and tractor fleet: the share of tractors – 28 percent, cultivators – 22, trailers – 19.8, cotton pickers – 13.8, the rest – 16.4 percent. They emphasized that the machines fleet could expand with the arrival of new modern machines produced by machine-building plants of the republic and imported from foreign countries. (Conclusions) The authors accepted the machine and tractor fleet of the cotton-textile cluster with the number of equipment 1660 units as rational. They proved that it ensured the implementation of all technological operations within agrotechnical terms.